Cost, time and quality aspects of primary schools in Singapore - Chan, Seng Kee. (2009)
This dissertation is primarily a report based on the findings from case studies of cost, time and quality aspects of 8 primary schools built in Singapore under the 4th Phase Primary School Building Programme (1991 to 1994). The report covers the examination and evaluation of the key factors, the effects of the key factors and the key issues and their impact on the process and method of implementation from inception to completion of the 8 primary schools.